Airflow and Temperature Simulation in a Big Cleanroom to Reduce Contamination in an HDD Manufacturing Factory - Jiranan Naosungnoen; Jatuporn Thongsri (My University, 2018)
Contamination is an important factor that must be well controlled at a stringent level of cleanliness. If it exceeds factory's specifications it shall contribute to poor quality products and product loss in the hard disk drive (HDD) manufacturing factory. This research used a CFD software, FLUENT to simulate the airflow pattern and temperature distribution in a big clean room to find the cause(s) of high contamination. The results of simulation revealed that there are areas in the production with vortex flow which caused high contamination similar to the actual measurement in that clean room. High air velocity that came out of the ULPA Filter at the ceiling above collided at the front of one Return grill nearby. It also caused high velocity vortex and high contamination in that area. To reduce the contamination, we closed one of the Return Grilled near that problematic area which could help reduce the vortex flow and the airflow pattern to be smoother than the previous clean room. Also, the contamination result showed a significant reduction in particle count. The temperature distribution after improvement action taken was unaffected and remained under the control. This research can help enhance a product quality and improve an efficacy of HDD manufacturing process
Keywords: Cleanroom; Factory (object-oriented programming); Contamination control; Augmented Reality Applications